TRADISI â€œMETHILâ€ SEBAGAI SALAH SATU WARISAN KEARIFAN LOKAL DI DESA KARANGMALANG KECAMATAN KASREMAN KABUPATEN NGAWI - Septiana, Inka (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
Abstract Culture is performed by human activities. And human culture are two things that can not be separated from one another. In some cultures there is a tradition that is carried out by the community. The tradition contains human activities in implementing something such as bancaan ceremony just before the rice harvest. Modernization is a time machine that is able to change a pattern of human behavior even able to give effect to a change in the existing local culture. Villagers are able to maintain the local tradition to modernization era certainly have a very strong reason. Key words: traditional culture, society, tradition, and modernization Pendahuluan